Valoración Grupo Argos : investment Banking Práctica Empresarial (2015)
Working on investment banking has been a strong but incredible experience, since I have learned lot of things (PowerPoint, Excel, and basically how to work). Investment Banking is not a sector for everyone, that’s true; but if you are one of the lucky ones who can handle it, it is with no shadow of doubt the best experience you can have. I feel really grateful of working on IB (Investment Banking) because it completed me, I evaluated lots of industries and I learned about lots of companies, and of course increased my English writing and understanding skills a 100%. On the other hand, since I worked on a multinational company, I also learned about how is the approving process on every transaction, how actually linked is the Colombia subsidiary with the other LatAm and though I did not work in the other areas, my team and I worked with them and this position helped me to understanding what areas I liked and not, and how all of them complement each other to make a huge Multinational Bank.